Contemporary Turkey at a Glance
VI, 202 p. 16 illus., 1 illus. in color.
Keywords: Turkey has witnessed significant social, cultural, and political change over the last decades. This transformation has manifested itself in all segments of society and resulted in the alteration of political ideologies and institutions. The twelve authors of this volume shed light on the complexities of a changing Turkey through an interdisciplinary perspective. Their application of novel conceptual approaches and methodologies make this book a unique contribution to the study of modern Turkey. Content Appropriating the Past.- Challenging Authority: Public Contention and Identity Negotiation.- Translocal Dynamics Target Groups Social, political, historical and cultural scientists The Editors Ayhan Kaya is Senior Professor of Politics at the Department of International Relations, Jean Monnet Chair of European Politics of Interculturalism, Director of the European Institute at Istanbul Bilgi University and a Member of Science Academy, Turkey. E. Fuat Keyman is Director of Istanbul Policy Center and Professor of International Relations at Sabancı University. Özge Onursal Beşgül is Assistant Professor at Istanbul Bilgi University in the Department of International Relations and the European Institute. Kristina Kamp is Ph.D. Candidate at Humboldt University of Berlin.